MicroRNAs miR-27a and miR-143 Regulate Porcine Adipocyte Lipid Metabolism - Wang, Tao (Molecular Diversity Preservation International (MDPI), 2011)
MicroRNAs (miRNAs) are non-coding small RNAs that play roles in regulating gene expression. Some miRNAs have been classed as epigenetic regulators of metabolism and energy homeostasis. Previous reports indicated that the miRNAs miR-27a and miR-143 were involved in lipid metabolism in human and rodents. To determine the roles of porcine miR-27a and miR-143 in adipocyte lipid metabolism, porcine adipocytes were cultured and allowed to induce differentiation for 10 days. The lipid-filled adipocytes were then transfected with miRNA mimics and inhibitors. We measured how the indicators of adipogenesis and adipolysis in porcine adipocytes were affected by the over-expression and by the inhibition of both miR-27a and miR-143. The results indicated that the over-expression of miR-27a could accelerate adipolysis releasing significantly more glycerol and free fatty acids than the negative control (P < 0.001), while the mimic of miR-143 expression, promoted adipogenesis by accumulating more triglycerides (P < 0.001) in the adipocytes. In addition, we demonstrated that there was good correlation (r > 0.98, P < 0.001) between the indicators of adipolysis in cell lysates and in the culture medium.